6th LICMAS 2022 Proceeding of selected articles in Arabic language - Editor, (AlQalam Journal of Medical and Applied Sciences, 2022)
This is the proceeding of the 6th Libyan Conference on Medical, Applied, and Social Sciences, contains full article in Arabic language